2022
DOI: 10.1177/02734753221093740
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous or Asynchronous Course: Business Students’ Perspectives on an Optimized Modality of Online Teaching and Learning

Abstract: Colleges and universities in the United States swiftly shifted campus-based classes to virtual spaces as a response to extended campus closures necessitated by the COVID-19 pandemic. Synchronous online courses were mandated as a replacement for traditional face-to-face classes in many higher education institutions. We understand that the benefits and drawbacks of synchronous courses need to be reviewed in this environment that has been heavily impacted by the pandemic. Thus, two survey studies were conducted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…Second, there was statistically significant evidence, in support of H2a, that students forced into remote learning during the pandemic were less likely to want to continue learning using the online modality (keeping all other factors constant). Our results echo Wu and You (2022), who observed that how a student evaluated a synchronous remote‐learning course overall shaped their preferences going forward.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Second, there was statistically significant evidence, in support of H2a, that students forced into remote learning during the pandemic were less likely to want to continue learning using the online modality (keeping all other factors constant). Our results echo Wu and You (2022), who observed that how a student evaluated a synchronous remote‐learning course overall shaped their preferences going forward.…”
Section: Discussionsupporting
confidence: 85%
“…However, regarding H2e, the importance of care of family members becomes significant in the multivariate analysis likely after any indirect mediating effects with other variables (such as household size) are included. This factor increased a student's desire to take an online course and aligns with recent news of students with caregiving responsibilities inclining toward permanent hybrid learning (Wu & You, 2022). However, since this variable was not significant in the univariate analysis, it is not emphasized in Table 4.…”
Section: Summary Of Results and Educational Implicationsmentioning
confidence: 76%
See 1 more Smart Citation
“…The existing research literature indicates that such forms of communication often drive high engagement due to its real-time nature; however, it can be highly challenging for the students as it enforces preestablished structures and learner discipline [29] [30]. Previous research on gender-based differences in synchronous and asynchronous learning suggests that male students typically favor the former.…”
Section: Discussionmentioning
confidence: 99%
“…Synchronous classes are educational spaces for real-time online connections; they allow for the sharing of activities between students and teachers; and they constitute a joint and interrelated teaching-learning academic experience. In this virtual-synchronous space, the teacher can assess the students' learning progress and provide feedback, based on the challenges that the student encounters (Wu & You, 2022;Moallem, 2015).…”
Section: Introductionmentioning
confidence: 99%